The Fragile X proteins Fmrp and Fxr2p cooperate to regulate glucose metabolism in mice. (30th December 2014) - Lumaban, Jeannette G.; Nelson, David L.
Abstract: Fragile X syndrome results from loss of FMR1 expression. Individuals with the disorder exhibit not only intellectual disability, but also an array of physical and behavioral abnormalities, including sleep difficulties. Studies in mice demonstrated that Fmr1, along with its paralog Fxr2, regulate circadian behavior, and that their absence disrupts expression and cycling of essential clock mRNAs in the liver. Recent reports have identified circadian genes to be essential for normal metabolism. Here we describe the metabolic defects that arise in mice mutated for both Fmr1 and Fxr2. These mice have reduced fat deposits compared with age- and weight-matched controls. Several metabolic markers show either low levels in plasma or abnormal circadian cycling (or both). Insulin levels are consistently low regardless of light exposure and feeding conditions, and the animals are extremely sensitive to injected insulin. Glucose production from introduced pyruvate and glucagon is impaired and the mice quickly clear injected glucose. These mice also have higher food intake and higher VO2 and VCO2 levels. We analyzed liver expression of genes involved in glucose homeostasis and found several that are expressed differentially in the mutant mice. These results point to the involvement of Fmr1 and Fxr2 in maintaining the normal metabolic state in mice.